(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND AND AIM Acute decompensation and death have been observed in patients with acute hepatitis E virus (HEV) infection and preexisting liver cirrhosis. However, the clinical, laboratory and histological features need to be fully characterised. METHODS Some of us recently described the histological presentation of hepatitis E in a large panel of liver tissue specimens. Here, we conducted a case-control study to investigate the clinical and laboratory features of the subset of patients with HEV-related acute-on-chronic liver failure (ACLF) and death. Each patient was matched to three control patients with histologically confirmed severe alcoholic hepatitis based on sex, age, total bilirubin, INR, serum creatinine and MELD score on admission. RESULTS Of 5 patients who died in a context of HEV-related ACLF, 3 (60%) were male and the median age was 66 years (range 51–76). Median alanine aminotransferase (ALT) at presentation was 2610 U/l (range 705–3134) and aspartate aminotransferase (AST) 2818 U/l (range 1176–8611). Liver function was heavily altered in all patients. Histological analyses revealed steatohepatitis on a background of cirrhosis, suggestive of an alcoholic or nonalcoholic origin. Based on histopathology, alcoholic hepatitis was initially suspected in two patients and corticosteroid treatment was initiated. Ribavirin was started in four patients. Median time from hospitalisation to death was 17 days (range 6–25 days). AST levels in patients with HEV-related ACLF were significantly higher as compared to the matched patients with severe alcoholic hepatitis. CONCLUSION Typical histopathological features of viral hepatitis may be absent in ACLF caused by HEV infection. HEV infection should be sought in acute decompensation of cirrhosis and ACLF even in the absence of histological changes suggesting viral infection.